THE ROLE OF ACTOR NETWORKS IN REFORESTATION POLICY IN INDONESIA - Rizky Ilhami (SEAN Institute, 2023)
Various approaches have been taken to explain the reforestation phenomenon that is occurring. The actor network dynamics perspective is a useful approach for mapping the power of actors who are networked in different spaces of power, in order to strengthen reforestation and even forest and environmental management at large. This research uses a qualitative approach with descriptive methods. The research results show that the role of actor networks in reforestation policy in Indonesia is very crucial. Coordination between the central government, regional governments and various related parties is fundamental in aligning policies with local conditions. In addition, providing adequate resources, such as funding, technology and workforce, as well as regular monitoring and evaluation, helps ensure the smooth implementation of reforestation programs. Thus, collaboration between various actors is expected to make a significant contribution to efforts to preserve the environment and improve the welfare of society in Indonesia.